Students´ reading ability moderates the effects of teachers´ beliefs on students´ reading progress - Egloff, Frank; Förster, Natalie; Souvignier, Elmar (Frontline Learning Research, 2019)
Teachers’ beliefs about teaching have been found to affect students’ learning growth. The aim of this study was to investigate effects of teachers’ constructivist and direct-transmissive beliefs on learners’ reading progress and whether these effects are influenced by prior student achievement. We measured constructivist and direct-transmissive beliefs of 29 teachers and the progress in reading fluency and reading comprehension of their students (N = 568) at eight points of measurement over one school year. Results of three-level latent growth curve modeling revealed that teachers’ constructivist beliefs were positively related to learners’ progress in reading fluency but had no general effect on growth in reading comprehension. Nevertheless, the relation between constructivist beliefs and individual learners’ progress in reading comprehension was affected by students’ level of ability. Teachers with stronger constructivist beliefs effected higher learning growth for high ability compared to low ability learners. No effects were found for direct-transmissive beliefs. Using longitudinal modelling of student learning, this study adds a more differentiated view to findings concerning the effects of teacher beliefs. Results show that effects vary depending on subject of learning (fluency vs. comprehension), and that effects of teacher beliefs may depend on students’ level of ability.